RESEARCH ACTION PARTICIPATION IN POLITICAL MARKETING 3.0. INTRAPERSONAL AND INTERPERSONAL EMOTIONAL INTELLIGENCE IN THE CASE OF PODEMOS AND CIUDADANOS - Reyero Simón, Laura (2020)
This article states that the application of the Participative Action Research (PAR) methodology is appropriate and useful as a market research instrument in the marketing field. par was, so far, only recognized in the field of education, except for authors such as Moreno (2005). The main research of this article, which was carried out between 2014 and 2016, confirmed the creation and consolidation of a new paradigm: Political Marketing 3.0.